A Planar-Gate Graphene Field-Effect Transistor Integrated Portable Platform for Rapid Detection of Colon Cancer-Derived Exosomes - Zaiyu Zhang; Luyang Zhang; Yuting Huang; Ziran Wang; Zhongjing Ren (Biosensors)
Early diagnosis of diseases would significantly increase the survival rate of cancer patients. However, current screening methods are complex and costly, making them unsuitable for rapid health diagnosis in daily life. Here, we develop a portable platform based on a planar-gate graphene field-effect transistor functionalized with polydopamine self-assembled film (PDA-GFET), capable of identifying colon cancer through the detection of EpCAM protein, which is expressed on colon cancer-derived exosomes, in clinical samples within 10 min. The PDA self-assembled film on the graphene and gate surface enhances the biosensor’s functionalization area while suppressing non-specific adsorption, thereby achieving detection limits as low as 112 particles/mL. In addition, the PDA-GFET-based detection platform was used to identify EpCAM protein in real clinical samples from healthy individuals and colon cancer patients within 10 min, and the two showed significant differences (p < 0.001). Results indicate that the proposed PDA-GFET-based detection platform is expected to be a potential tool for the early diagnosis of colon cancer.